Effect of ball weight on speed, accuracy, and mechanics in cricket fast bowling - Wickington, K. L.; Linthorne, N. P. (Sports, 2017)
The aims of this study were: (1) to quantify the acute effects of ball weight on ball release speed, accuracy, and mechanics in cricket fast bowling; and (2) to test whether a period of sustained training with underweight and overweight balls is effective in increasing a player`s ball release speed. Ten well-trained adult male cricket players performed maximum-effort deliveries using balls ranging in weight from 46% to 137% of the standard ball weight (156 g). A radar gun, bowling target, and 2D video analysis were used to obtain measures of ball speed, accuracy, and mechanics. The participants were assigned to either an intervention group, who trained with underweight and overweight balls, or to a control group, who trained with standard-weight balls. We found that ball speed decreased at a rate of about 1.1 m/s per 100 g increase in ball weight. Accuracy and bowling mechanics were not adversely affected by changes in ball weight. There was evidence that training with underweight and overweight balls might have produced a practically meaningful increase in bowling speed (>1.5 m/s) in some players without compromising accuracy or increasing their risk of injury through inducing poor bowling mechanics. In cricket fast bowling, a wide range of ball weight might be necessary to produce an effective modified-implement training program